SAT0261 FEATURES AND RISK FACTORS OF SERIOUS INFECTIONS IN ANCA ASSOCIATED VASCULITIS: LONG TERM FOLLOW UP OF 186 PATIENTS. (2nd June 2020) - Ince, B.; Bektas, M.; Kemik, F.; Aytun, A. E.; Yalçinkaya, Y.; Artim-Esen, B.; Gül, A.; Ocal, M. L.; Inanc, M.
Abstract : Background: Serious infections (SI) are one of the main complications in patients with ANCA associated vasculitis (AAV). Objectives: We planned to investigate the prevalence, features and risk factors of SI in our AAV cohort during follow-up. Methods: Outpatient and hospital data of patients diagnosed with granulomatous polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatous polyangiitis (eGPA) between 1999 and 2019 according to Chapel Hill Consensus Criteria and followed up at least 6 months in our vasculitis clinic were evaluated. Development of sepsis, requirement for intravenous (IV) antibiotherapy and / or hospitalization during infection episodes were considered as SI. Chi-square, student's t-test and logistic regression analysis were used for statistical analysis. Results: Study was conducted with 186 (53.6% female) patients with adequate follow-up data. Mean age of diagnosis was 54.3±14, 5 (23-79), mean follow-up duration was 86, 4 ± 54, 3 (6-251) months. Number of GPA, MPA and eGPA patients were 132 (71%), 42 (22, 5%) and 12 (6, 5%), respectively. IV cyclophosphamide (CYC) was used in 148 (79, 6%), azathioprin in 105 (56, 5%), rituximab (RTX) in 69 (%37, 1), methotrexate in 29 (15, 6%) and mycophenolate mofetil in 14 (7, 5%) patients. Number of patients developed SI was 66 (34.7%), total SI episode was 86, patients who had multiple episodes was 15. All SI is shown in Table-1. Bacterial pneumonia was the most common diagnosis and 26 of SI (30.2%) were considered as opportunistic (systemic viral, parasite, fungus) infections. Thirty-one of patients developed SI (40, 7%) in the first year after diagnosis. SI were observed more frequently in the presence of major organ involvement (kidney, lung, neurological) (65/173 vs. 1/13 p = 0.02 OR = 8.7 95% CI 1.06-64.4). Diffuse alveolar hemorrhage (DAH) was associated with SI in multivariate analysis (12/52 vs. 0/34 p=0.007 OR=1.6 95% CI 1.3-1.96). Cumulative CYC dose was significantly higher in patients with SI (14, 2±21 vs. 8.2±13.9 p=0.045). During maintenance, patients treated with RTX had significantly more SI (18/53 vs. 17/99 p=0.19 OR=3, 3 95% CI 1, 55- 7, 07). Hypogammaglobulinemia (HIgG) (IgG<700 mg/dL) was present in 12 (14%) SI episodes. HIgG was associated with SI in RTX-treated patients (5/13 vs. 7/47 p=0.03 OR=4.2, CI=1-16.5). Hospitalization need for SI was 65%. Disease flares (34/128 vs. 32/62 p = 0.001 %95 CI = 2.9 95% CI 1.6-5.6) and organ damage presence were more common (64/65 vs. 109/125 p = 0.01 95% OR= 8.9 95% CI 1.1-68.9) in patients with a history of SI in multivariate analysis. SI was confirmed as cause of death in three cases. Conclusion: Long-term follow-up results of a single center cohort of AAV patients revealed that approximately one third of patients developed SI, most frequently in the first year of treatment. During the maintenance period, the risk of SI continues. Cumulative CYC dosage and maintanence with RTX is associated with SI, especially in patients who developed hIgG. Major organ involvement, disease flares and organ damage are significant risk factors for SI. In this regard, protection measures (vaccination, prophylaxis) should be reviewed and the quality of follow-up should be improved. Disclosure of Interests: None declared